Variants Of Lichen Planus Associated With Thyroid Disorder- A Case Report (Journal of Pharmaceutical Negative Results, 2022)
Lichen planus is an idiopathic chronic inflammatory skin condition , Lichen planus pigmentosus (LPPigmentosus) and lichen planopilaris (LPP) are two clinically and histologically distinct forms of lichen planus (LP). LPPigmentosus presents with sudden onset hyperpigmented macules and patches. On the other hand, LPP is a scarring follicular variant of lichen planus that presents with progressive, permanent patches of alopecia.Here we report a case of 62-year -old women with history of hypothyroidism and coexistence of LPPig with LPP . The association of pre-existing autoimmune thyroid disorder with lichen planopilaris is a well known factor.The presence of hypothyroidism in our patient not only predisposed to Lichenplanopilaris also to Lichenplanopigmentosus